REKONSTRUKSI MANAJEMEN MARKETING PENDIDIKAN ISLAM BERBASIS DIGITAL BRANDING SYARIAH - Saefuddaulah Mehir; Toto Sukarnoto; Ibnu Hajar Al Asqolani (Universitas Islam Bunga Bangsa Cirebon, 2022)
The rapid advancement of digital technology has fundamentally reshaped how educational institutions communicate their value propositions to prospective students and stakeholders. Islamic educational institutions, however, have been considerably slow in adapting their marketing management strategies to this digital transformation, particularly in harmonizing contemporary digital branding practices with Shariah principles. This study aims to reconstruct a marketing management model for Islamic education grounded in the concept of digital branding Shariah an integrative framework that synthesizes digital marketing strategies with the ethical and theological imperatives of Islamic teachings. Employing a systematic library research methodology, this study analyzed and synthesized relevant academic literature, including reputable national and international journals and reference books published within the last five years. Data analysis utilized the Miles and Huberman interactive model. The findings propose a reconstructed model comprising four interrelated dimensions: Shariah-compliant digital identity, value-based content marketing, halal digital community engagement, and ethical digital accountability. This model offers a contextually grounded and operationally feasible pathway for Islamic educational institutions to enhance their competitiveness while preserving their identity and integrity.